2001
DOI: 10.1017/s0012162201000044
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns of rhythmic suck and swallow in preterm infants

Abstract: Twenty healthy preterm infants (gestational age 26 to 33 weeks, postmenstrual age [PMA] 32.1 to 39.6 weeks, postnatal age [PNA] 2.0 to 11.6 weeks) were studied weekly from initiation of bottle feeding until discharge, with simultaneous digital recordings of pharyngeal and nipple (teat) pressure and nasal thermistor and thoracic strain gauge readings. The percentage of sucks aggregated into 'runs' (defined as > or = 3 sucks with < or = 2 seconds between suck peaks) increased over time and correlated significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
12

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 21 publications
5
95
1
12
Order By: Relevance
“…While there has been discussion regarding whether the maturation of suck-swallow-breathe coordination is related to the infant's PMA or experience, Simpson et al 5 recently found that experience may play the more important role. 18,19 While there was a trend toward starting oral feedings earlier in our study, the difference was not statistically significant. Because this study included the first patients put on the clinical pathway, relative inexperience in assessing signs of feeding readiness may have kept some staff from starting oral feedings at an earlier PMA.…”
Section: Discussioncontrasting
confidence: 64%
“…While there has been discussion regarding whether the maturation of suck-swallow-breathe coordination is related to the infant's PMA or experience, Simpson et al 5 recently found that experience may play the more important role. 18,19 While there was a trend toward starting oral feedings earlier in our study, the difference was not statistically significant. Because this study included the first patients put on the clinical pathway, relative inexperience in assessing signs of feeding readiness may have kept some staff from starting oral feedings at an earlier PMA.…”
Section: Discussioncontrasting
confidence: 64%
“…This stabilization correlates more with PMA than with postnatal age. 20 The studies by Gewolb et al 20 show that rhythm is an integrated part of maturation. Quereshi et al 16 expand on this theme by explaining that the changes observed at 1 month of age may be an adaptation of the drinking pattern to include volition, with longer sequences and a larger number of sucking movements.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, it is likely that these behavioral patterns are congenital rather than acquired. 20 However, the rhythmicity of the suck-swallow-breath relationship depends also on nonmaturational factors, such as satiety, behavioral state and milk flow. Milk flow depends on the hole size of the nipple (bottle feeding), the milk ejection reflex (in breastfeeding), but it also depends on the infant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…155 At about 32 weeks gestation, an infant will begin to display bursts of sucking, and by 34 weeks a rhythmic suck, swallow and breathe pattern is developing. [156][157][158][159][160][161] Non-nutritive sucking will transition towards more effective nutritive sucking, concurrent with state of alertness and increasing gestational age. 162 Non-nutritive sucking with pacifier use may facilitate the transition to effective nutritive sucking at 32 to 34 weeks gestation.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%